A novel multiscale porous composite structure for sound absorption enhancement. (15th November 2021) - Liu, Qihang; Liu, Xuewei; Zhang, Chuanzeng; Xin, Fengxian
Abstract: A novel multiscale porous composite structure is proposed in this paper, which combines the advantages of two different micro-porous materials and distributed meso-pores to enhance the sound absorption performance. The proposed porous composite structure consists of a micro-porous material matrix with periodically distributed meso-pores, in which a second micro-porous material layer is introduced as an interlayer between the matrix and the meso-pores. Numerical simulations based on COMSOL Multiphysics are performed to validate the developed theoretical model and good agreements are achieved. The proposed novel composite structure shows an obvious enhancement of the sound absorption performance compared with the double porosity material without the interlayer. The sound absorption mechanism inside the porous composite structure is also explored through the analysis of the distributions of the sound pressure and the energy dissipation. Besides, the effects of the key multiscale parameters on the sound absorption performance are studied. The results demonstrate that by altering these parameters, the acoustic impedance matching between the porous composite structure and air can be improved, which leads to a further enhancement of the sound absorption performance. The theoretical and numerical models and the corresponding results presented in this work provide a novel idea and an efficient analysis framework for the multiscale design and optimization of advanced porous composite structures to improve the sound absorption performance of the conventional porous materials.